Pseudospherical Bismuth Oxychloride-Modified Carbon Paste Electrode for the Determination of Quinine in Beverages - Tijana Mutić; Vesna Stanković; Miloš Ognjanović; Vladimir B. Nikolić; Guanyue Gao; Neso Sojic; Dalibor Stanković (Electrochem)
The extensive use of the alkaloid quinine (QN) in the cosmetic and food industries has induced major concerns relating to its impact on human health, considering its potential toxicity. Therefore, developing sensitive and selective electrochemical sensors is crucial for monitoring QN in environmental, food, and pharmaceutical samples. To respond to this need, a surfactant-supported green synthesis approach, based on a straightforward, organic solvent-free hydrothermal method was employed to synthesize highly crystalline pseudospherical bismuth oxychloride (BiOCl) nanoparticles. This material was used for the enrichment of carbon paste electrodes and its further utilization for the detection and quantification of quinine. They have superior electrocatalytic performance, due to their size and morphology, and facilitate the interactions of the target with the electrode surface. Under optimal operating conditions, differential pulse voltammetry demonstrated a remarkable feature: a broad linear working range of 10 to 140 μM, a detection limit of 0.14 μM, and a high sensitivity of 1.995 μA μM−1 cm−2. The suggested method’s satisfactory sensitivity, along with its good stability, repeatability, and reproducibility, strongly point to a possible use for identifying quinine in real samples.